(untitled) (Biodiversitas Journal of Biological Diversity, 2009)
Gloriosa superba L. is an important medicinal plant of Asia and Africa. It is used in diseases, like cancer, gout, scrofula and act as antipyretic, antihelmintic, purgative and antiabortive. It is a source of colchicines and colchicocides, which are very costly, being highly demanded by pharma industries. Due to excessive use of the plant for diverse medicinal purposes the species is on the verge of extinction and included in Red Data Book. The strenuous efforts of botanists, biotechnologists, policy makers and conservationists are required. It is a matter of great concern to conserve this plant otherwise we will be loosing it by 2020.The present review is focused on current status of the genus, source of alkaloids, poisonous nature, the strategies for its conservation and future perspectives of G. superba.